Humor as a resource for confronting wartime challenges - Khraban, Tetiana (Lesya Ukrainka Eastern European National University, 2023)
The aim of the study is to identify Ukrainian social media audiences’ preferences for humor styles to maintain/enhance their psychological resilience in different periods of wartime. Discourse analysis developed in the framework of social constructionism was used for collecting and analyzing data. We argue that 1) the preferences in humor styles is directly influenced not only by contextual factors and the duration of the stressor, but by the audience’s psycho-emotional state and its intentions; 2) aggressive humor style is especially in demand in the period of adaptation to the traumatic event, but the audience can use its various forms depending on their effectiveness for a particular purpose. Thus, black humor is productive for emotional venting of negative emotion of anger and reducing of emotional distress; disparagement humor is effective for formation of collective identity and increasing of optimism; 3) self-enhancing humor style can serve as a sign of positive shifts in the process of adaptation to a psychologically traumatic situation, and restoration of the population’s psychological stability; 4) self-defeating humor style is actualized in wartime as a form of adaptive humor, since it promotes a sense of community (belonging to a group) and identification through the experience of a shared stressful situation; and also positively correlates with self-esteem as a result of an individual’s demonstration of his/her ability to maintain self-control and to keep calm and carry on when faced with stressful situations.
Keywords: emotion; humor; wartime stress; traumatic experience